E-Learning Responsif Berbasis Laravel untuk Mendukung Pembelajaran Daring di SMP Negeri 1 Kudus - Yahya, Ahmad Dimasyqi (UNIVERSITAS RAHARJA, 2025)
The advancement of information technology has driven educational institutions to adapt, particularly in implementing responsive and integrated online learning. This study aims to design and develop a Laravel-based e-learning system at SMP Negeri 1 Kudus to support digital teaching and learning processes. The system was designed using the Waterfall software development method, which includes requirement analysis, system design, implementation, testing, and maintenance. This system provides key features such as user management, learning material management, assignments, exams, and grade reports, accessible via both desktop and mobile devices. During development, web technologies such as HTML, CSS, JavaScript, and the MySQL database were utilized. Testing results showed that the application operated according to specifications and positively impacted the effectiveness of online learning, particularly in enhancing interactions between teachers and students. Additionally, the system is responsive and supports cross-device accessibility, facilitating students and teachers in various situations. This research is expected to offer an innovative solution to overcome the limitations of conventional learning, support digital transformation in education, and provide a more interactive and adaptive learning experience in line with technological advancements.